Implementation of Al-Islam and Kemuhammadiyahan (AIK) Learning Development through Al-Islam Intensive Lecture Training (KIAI): Implementasi Pengembangan Pembelajaran Al-Islam dan Kemuhammadiyahan (AIK) Melalui Pelatihan Kuliah Intensif Al-Islam (KIAI) - Hidayat, Yayat (Journal of Islamic and Muhammadiyah Studies, 2024)
This research is expected to be able to encourage the development of al-Islam and Kemuhammadiyahan learning that is being the characteristic in Muhammadiyah Universities. The purpose of this research is to explore the implementation of the development of al-Islam and Kemuhammadiyahan (AIK) learning through the al-Islam Intensive Lecture Training (KIAI) at the Students of Faculty of Education and Language Studies, Muhammadiyah University of Yogyakarta. The object of this research was The student in Faculty of Education and Language Studies and Al-Islam Intensive Lecturer (KIAI). This study used descriptive-analytic method by collecting information and applying observation, In-depth interview and documentation. Highlights: Exploration Focus: Investigating AIK learning’s implementation via KIAI at Muhammadiyah University, Yogyakarta, emphasizing development. Methodology: Descriptive-analytic approach utilizes observation, interviews, and documentation for comprehensive insight into AIK learning. Educational Impact: Study on Faculty of Education and Language Studies students and KIAIs highlights AIK learning’s significance in nurturing Islamic and Muhammadiyah characteristics in university education. Keywords: Implementation of Al-Islam, Kemuhammadiyahan Learning, KIAI Training